Learning to relax - Benton, Gail; Benton, Gail (California : David Watts Production [production company] ; California : Aims Media Van Nuys [distributor], 1987)
Five simple relaxation techniques are illustrated : deep breathing, muscle relaxation, stretching, clearing the mind, and visualization. The program offers methods for bringing stress under control
Copy available in DVD format
Executive producer, David Watts ; writer, Danial Gunther ; editor, Ron Colberg
Speakers: David Watts, Kenneth R. Pelletier
Keywords: Learning, Psychology of